Intratumoral regulatory T cells with higher prevalence and more suppressive activity in hepatocellular carcinoma patients - Wu, Han; Chen, Pei; Liao, Rui; Li, Yi-Wei; Yi, Yong; Wang, Jia-Xing; Cai, Xiao-Yan; He, Hong-Wei; Jin, Jian-Jun; Cheng, Yun-Feng; Fan, Jia; Sun, Jian; et al. (Journal of gastroenterology and hepatology, 2013)
Background and Aim Regulatory T cells (Treg) play a vital role in immunosuppressive crosstalk; however, Tregs from different locations lead to different clinical outcomes. Our aim was, therefore, to compare the prevalences and suppressive phenotypes of Tregs in the peripheral blood, peritumor, and intratumor of patients with hepatocellular carcinoma (HCC). Methods The frequencies and phenotypes of CD4+CD25+CD127low/−CD49d− Tregs in the periphery, peritumor, and intratumor of 78 HCC patients and 12 healthy controls were evaluated by flow cytometry. Treg‐cell suppressive activity was determined using an in vitro CD154 expression assay. Tregs from tumor and paired peritumor were then hybridized using an Agilent whole genome oligo microarray, and selected genes were validated by real‐time polymerase chain reaction. Functional analysis of the microarray data was performed using Kyoto Encyclopedia of Genes and Genomes and Gene Ontology analyses. Results Intratumoral Tregs exhibited higher frequencies and more suppressive phenotypic functions than those in peritumor and periphery, whereas there was no difference between the latter two. Functional analysis showed that complement cascades, p53, and glycosylphosphatidylinositol‐anchor biosynthesis pathways were significantly upregulated in intratumoral Tregs; the salivary secretion pathway was significantly downregulated in intratumoral Tregs, and immune cells and tumor‐immuno‐related Gene Ontology terms were significantly affected. Conclusions Tregs in different locations exhibited different functional statuses. A higher prevalence and more suppressive phenotype suggested a critical role for intratumoral Tregs in the formation of multicellular immunosuppressive networks. HCC immunotherapy may be improved, therefore, by specific locational Tregs elimination or suppression.